Wireless networking : understanding internetworking challenges - Burbank, Jack L.; Andrusenko, Julia; Everett, Jared S.; Kasch, William T. M. (Hoboken, NJ : Wiley ; Piscataway, NJ : IEEE Press, 2013)
"This book focuses on providing a detailed and practical explanation of key existing and emerging wireless networking technologies and trends, while minimizing the amount of theoretical background information. The book also goes beyond simply presenting what the technology is, but also examines why the technology is the way it is, the history of its development, standardization, and deployment. The book also describes how each technology is used, what problems it was designed to solve, what problems it was not designed to solve., how it relates to other technologies in the marketplace, and internetworking challenges faced withing the context of the Internet, as well as providing deployment trends and standardization trends. Finally, this book decomposes evolving wireless technologies to identify key technical and usage trends in order to discuss the likely characteristics of future wireless networks"--
"Focuses on real-life networking challenges and solutions"--Provided by publisher.
5.2 Usage.
Includes bibliographical references (pages 632-649) and index.
Online resource; title from ebook title screen (ebrary platform, viewed February 14, 2014).
Keywords: Internetworking (Telecommunication); Computer networks; Wireless communication systems; Computer networks; Internetworking (Telecommunication); Wireless communication systems; TECHNOLOGY & ENGINEERING -- Mobile & Wireless Communications; COMPUTERS -- Data Transmission Systems -- General; COMPUTERS -- Networking -- Vendor Specific; Computer networks; Internetworking (Telecommunication); Wireless communication systems; Electronic books